A mixed integer linear programming model for integrating thermodynamic cycles for waste heat exploitation in process sites. (15th September 2016) - Oluleye, Gbemi; Smith, Robin
Highlights: MILP model developed for integration of waste heat recovery technologies in process sites. Five thermodynamic cycles considered for exploitation of industrial waste heat. Temperature and quantity of multiple waste heat sources considered. Interactions with the site utility system considered. Industrial case study presented to illustrate application of the proposed methodology. Abstract: Thermodynamic cycles such as organic Rankine cycles, absorption chillers, absorption heat pumps, absorption heat transformers, and mechanical heat pumps are able to utilize wasted thermal energy in process sites for the generation of electrical power, chilling and heat at a higher temperature. In this work, a novel systematic framework is presented for optimal integration of these technologies in process sites. The framework is also used to assess the best design approach for integrating waste heat recovery technologies in process sites, i.e. stand-alone integration or a systems-oriented integration. The developed framework allows for: (1) selection of one or more waste heat sources (taking into account the temperatures and thermal energy content), (2) selection of one or more technology options and working fluids, (3) selection of end-uses of recovered energy, (4) exploitation of interactions with the existing site utility system and (5) the potential for heat recovery via heat exchange is also explored. The methodology is applied to an industrial case study. Results indicate a systems-oriented design approach reduces waste heat by 24%; fuel consumption by 54% and CO2 emissions by 53% with a 2 year payback, and stand-alone design approach reduces waste heat by 12%; fuel consumption by 29% and CO2 emissions by 20.5% with a 4 year payback. Therefore, benefits from waste heat utilization increase when interactions between the existing site utility system and the waste heat recovery technologies are explored simultaneously. The case study also shows that the novel methodology can select and design optimal solutions for waste heat exploitation which are technically, economically and environmentally feasible from a range of technology options, heat sources and end-uses of recovered energy.